(untitled) (Third Sector Social Economic Review, 2024)
In this study, it is aimed to examine the relationship between marketing sales and distribution expenses and business performance. To achieve this goal, the relationship between the expenses incurred by the business for marketing activities and company performance was investigated at the level of different variables. The variables considered in the study are booked into three categories: Dependent factors, Independent factors, and Control factors. Tobin’s Q mileage, Earn on Total Assets (ROA), and Earn on Equity (ROE) data were used as dependent variables. Marketing Expenditures and BIST Textile Index Return were accepted as independent variables. Total Sales and Debt Ratio were used as control variables. 5-year company data for the periods 2019-2023 were used in the research. The data used in the study were taken from the Public Disclosure Platform (KAP). In the research, 18 companies included in the Borsa Istanbul (BIST) Textile and Leather Index, where marketing and promotion expenses are extremely important, were included. According to the results obtained from the research, it has been determined that marketing and promotional activities expenditures have a positive impact on company performance. It has been determined that there is a positive relationship between expenses arising from marketing activities and company performance.